Effects of microtopography and water table on Sphagnum palustre L. in subtropical high mountains and implications for peatland restoration. (3rd April 2019) - Li, Ting-Ting; Wang, Zheng-Xiang; Bu, Gui-Jun; Lin, Li-Qun; Lei, Yun; Liu, Chang-Yong; Yang, Lan-Fang; Zheng, Cheng-lin
ABSTRACT: Introduction . Human disturbance has recently led to increasingly serious destruction of Sphagnum L. wetlands in subtropical high mountains, resulting in an urgent need for wetland restoration. Methods . Through a field experiment conducted in western Hubei Province, China, the effects of four different microtopographic types [concave surface, convex surface, concave and convex surface (CC surface), and flat surface] and water table depth (0 to −30 cm) on three growth indicators (number of capitula, coverage and biomass) of Sphagnum palustre L. were examined. The objective was to identify the optimal hydrological conditions for S. palustre growth and thus facilitate its rapid recolonisation and restoration of these wetlands. Key results . The results showed that different microtopographic conditions significantly influenced S. palustre growth. Among them, S. palustre in the CC surface showed the worst growth, while no significant differences existed among the other three microtopographic types. Additionally, as the water table increased, the growth of S. palustre increased, but long-term flooding impeded growth. The water table affected S. palustre growth via effects on its tissue water content. Conclusions . Microtopographic reshaping was not essential for the success of S. palustre recolonisation, and microtopography that maintained the water table to within −10 cm of the surface without flooding were best, independent of the microtopographic types. In addition, the growth patterns of S. palustre changed with changes in the environment, which may be related to its long-term adaptation to conditions of a lower water table.